Hepatic Rupture in HELLP Syndrome: Report of Two Patients and a Review of Peripartum Surgical Care and Transfusion - Sarah N. Larson; Trevor F. Killeen; Laura Bowman; Sruthi Shankar; Emily Stock; Lindsay Welton; James V. Harmon Jr. (Clinical Case Reports)
ABSTRACT Herein, we report the cases of two patients with hemolysis, elevated liver enzymes, and low platelets syndrome who underwent emergent Cesarean sections that were complicated by massive hemorrhage due to undiagnosed hepatic rupture. Intraoperative General Surgery team intervention, early activation of massive transfusion protocol, hemostatic resuscitation, and transfer to ICU resulted in the survival of both patients.